Selective coronary angiography, percutaneous coronary intervention and asymptomatic peri-procedural myocardial injury - Gřiva, Martin; Šťastný, Jiří; Kopřiva, Petr; Slabák, Martin; Coufal, Zdeněk; Jarkovský, Jiří; Svoboda, Michal; Šálek, Tomáš; Súkupová, Lucie; Táborský, Miloš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2019)
BACKGROUND: While there have been a number of studies reporting the incidence and implications of elevated troponin levels after percutaneous coronary intervention (PCI), the body of information about the incidence, associations, and implications of elevated troponin levels following coronary angiography (CAG) is limited. MATERIALS AND METHODS: A total of 220 consecutive patients with stable coronary artery disease or intermediate or low-risk acute coronary syndrome without persistent ST-segment elevation (NSTE-ACS) were included in our study. High-sensitivity cardiac troponin I (hs-cTnI) levels were measured before and after coronary angiography (CAG) in patients with or without PCI and correlated with a number of clinical variables. RESULTS: Hs-cTnI elevations above the 99th percentile upper reference limit (URL), or above 20% of the initially positive, yet already declining values, were found in 60 (37.2%) patients after CAG and in 45 (76.2%) patients undergoing PCI. Significant correlations of hs-cTnI elevation were found with the following variables: volume of contrast, fluoroscopy time, dose-area product, amount of contrast agent injected directly into the coronary arteries, total time of balloon dilation and the number and total length of implanted stents (P<0.001 for all). CONCLUSION: While an asymptomatic elevation of hs-cTnI is a common finding after PCI, it does occur, quite surprisingly, also after CAG. Despite contradictory views regarding the clinical relevance of asymptomatic post-procedural elevated hs-cTnI levels, it is generally believed that a mild elevation is not associated with an increased risk. Still, it may pose a diagnostic quandary following a successful interventional procedure and even more so after an uncomplicated CAG. TRIAL REGISTRATION: Clinicaltrials.gov - NCT02960321.
Keywords: perioperační péče; Coronary Angiography; senioři nad 80 let; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Percutaneous Coronary Intervention; Troponin; nemoci koronárních tepen; Perioperative Care; Coronary Artery Disease; mužské pohlaví; biologické markery; koronární angioplastika; ženské pohlaví; lidé; Biomarkers; Aged; senioři; Male; troponin; koronární angiografie; Female